2017
DOI: 10.1542/peds.2016-2848
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Manifestations of Celiac Disease Autoimmunity in Young Children

Abstract: BACKGROUND AND OBJECTIVES Psychological symptoms can be associated with celiac disease; however, this association has not been studied prospectively in a pediatric cohort. We examined mother report of psychological functioning in children persistently positive for tissue transglutaminase autoantibodies (tTGA), defined as celiac disease autoimmunity (CDA), compared with children without CDA in a screening population of genetically at-risk children. We also investigated differences in psychological symptoms base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 16 publications
2
29
0
1
Order By: Relevance
“…In a study of children with newly diagnosed CD, approximately 20% had subclinical neurological abnormalities such as peripheral polyneuropathy and cortical atrophy (37) . A recent study showed that 3.5-year-old children with persistently positive tTG antibodies on a gluten-containing diet were more likely to manifest behavioral problems, including anxiety, depression and aggressiveness, when compared to those with negative antibody tests (38) . The pathogenesis of the neurologic symptoms is unclear but they tend to resolve on a GFD (39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of children with newly diagnosed CD, approximately 20% had subclinical neurological abnormalities such as peripheral polyneuropathy and cortical atrophy (37) . A recent study showed that 3.5-year-old children with persistently positive tTG antibodies on a gluten-containing diet were more likely to manifest behavioral problems, including anxiety, depression and aggressiveness, when compared to those with negative antibody tests (38) . The pathogenesis of the neurologic symptoms is unclear but they tend to resolve on a GFD (39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
“…Celiac children with persistently elevated tTG IgA scored significantly higher for anxiety, depression, aggressive behaviors, and sleep problems. Initiation of the GFD did not appear to have an impact on the psychological functioning of the patients in this study (though very young children) [ 62 ]. Another study by Simsek et al in 2015 assessed the rates of psychiatric symptoms in newly diagnosed celiac pediatric patients aged 9 to 16 years old as compared to age and sex matched healthy controls that had presented for routine checkup.…”
Section: Behavioral Changes and Psychiatric Disordersmentioning
confidence: 99%
“…We found 15 studies that evaluated psychiatric disorders in children or young adults with CD, 11 of which were conducted in clinical-based settings and four were conducted in community-based settings ( Table 1 ). Studies were published between 1997 and 2018 [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Most studies ( n = 12) were cross-sectional, although one of them included a subsequent longitudinal phase [ 41 ].…”
Section: Resultsmentioning
confidence: 99%